STUDENTS MATHEMATICAL COMMUNICATION SKILLS ON COOPERATIVE LEARNING OF TGT TYPE TO SET MATERIAL - Meinar Yuari Salsabil; Siti Inganah; Yus Mochamad Cholily (MEJ (Mathematics Education Journal), 2017)
This study aims to describe students' mathematical communication skillsboth oral and written. The communication ability is observed through theapplication of cooperative learning model type TGT for set theory. Theresearch design was qualitative descriptive. The subjects of the study were 17students of class VII-B. The learning material were lesson plan,discussion group, game group, worksheet, game question, and written test.The research instruments were observation sheet of teacher activity, writtenand oral mathematical communication ability. The results of the study at thefirst meeting showed that the ability of oral mathematical communication hadsufficient category and written had low category. The second meeting of oralmathematical communication skills had sufficient category and written wasbetter than before. Oral mathematical communication improved at the thirdmeeting, while written in the low category. The fourth meeting was increasedin the ability of oral and written mathematical communication, for high oralmathematical communication and written with high category as well. Thestudents' mathematical communication skills from the first to fourthmeetings had increased. The average overall ability of oral and writtenmathematical communication was sufficient